Situation analysis: MedLung and the TAM-SAM-SOM model - Denault, Jean-François (Henry Stewart Talks, 2020)
This case study demonstrates the use of the TAM-SAM-SOM model by applying it to MedLung, illustrating the principle of calculating market size and forecasted growth when performing a situation analysis.